ASUHAN KEHAMILAN DALAM PERSPEKTIF BUDAYA JAWA DI DESA LABUHAN LABO KECAMATAN PADANGSIDIMPUAN TENGGARA KOTA PADANGSIDIMPUAN TAHUN 2015 - Juwarni, Sri (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Social and cultural conditions (customs) and environmental conditions (geographical conditions) affects reproductive health. Cultural situation this case customs at this time is not conducive for help seeking behavior in reproductive health issues in Indonesia. Java community strongly believe in myths developed by the predecessor. The Javanese culture for the community is an important thing,This study aims to determine pregnancy care in the perspective of Javanese culture the village of Labuhan Labo District of Southeast Padangsidimpuan Padangsidimpuan City. This type of research is qualitative descriptive study. Informants   in this study is that people who understand the culture of Java in pregnancy care, amounting to 8 people. Collecting data using in-depth interviews conducted with, by means of data collection is interview, and a  tape recorder. Results showed the care pregnancy in Labuhan Labo still influenced habit cultural of Java that includes 5 theme al: place and health services in the midwife and healer, the myth about the nutrition of pregnant women, the myth of pregnancy care with customs abdominal massage and seven monthly ritual, taboo / behavior of pregnant women and husband as well health information. Padangsidimpuan  City  Health Department, particularly the health center IV Pijorkoling Pal and related health team must give Information Education Communication (IEC) to Community appropriately, so to increase knowledge about pregnancy care in accordance the espoused culture. Shamans to follow skills in assisting the examination of pregnant women, in respect of utilizing the many people who still shaman in Antenatal care services in particular